Binary Mixtures of Sodium Salt of Ibuprofen and Selected Bile Salts: Interface, Micellar, Thermodynamic, and Spectroscopic Study - Abdul Rub, Malik; Azum, Naved; Asiri, Abdullah M (Journal of chemical and engineering data, 2017)
With the intention to explore bile salts applications as drug delivery vehicles, the mixed interfacial as well as micellar behavior of the sodium salt of ibuprofen (NaIbuF) and bile salts mixtures in aqueous/electrolyte solutions has been evaluated by tensiometric method at 298.15 K. Bile salts (sodium cholate (NaC) and sodium deoxycholate (NaDC)) used in the present study are anionic in nature and form small micelles. Various theoretical models such as Clint, Rubingh, and Rosen were utilized to acquire information concerning the nature of interaction among the components in the solution as well as at the interface. Because of the presence of inorganic salt (100 mmol·kg–1 NaCl) a decrease in the surface charge of the micelles takes place and ensuing micellization occurs at poorer concentration. The value of the micellar mole fraction (X 1 m) is found to be greater for NaIbuF + NaDC mixtures in comparison to NaIbuF + NaC mixtures, signifying that participation of NaDC is greater in mixed micelles as compared to NaC. An attractive interaction was obtained in the micelle and at the interface, because it is obvious from interaction parameters (βm, βσ). The values of ΔG 0 m for all systems was negative in the absence as well as in the occurrence of salt. Micelle aggregation number (N agg), estimated by means of steady-state fluorescence quenching studies, suggests that the contribution of bile salts was always greater than that of the NaIbuF. The micropolarity (I 1/I 3), Stern–Volmer binding constants (K sv), and dielectric constant (D exp) of mixtures also supported the synergistic behavior of the drug–bile salts mixed systems.